Effectiveness of Diabetes Mellitus Type 2 Management in Prolanis Participants at the BPJS Kesehatan Sibolga - Sitompul, Ester Maria Suzanne; As Shidieq, Firdaus Hafidz (Jurnal Jaminan Kesehatan Nasional, 2024)
BPJS Kesehatan aims to improve the health of participants suffering from Type 2 DM through the Chronic Disease Management Program “Prolanis” (Program Pengelolaan Penyakit Kronis) strategy implemented at Primary Health Care (PHC). Program success is measured by the outcomes of controlled Fasting Blood Sugar status and the cost-effectiveness of Prolanis. This research was conducted to determine the cost-effectiveness of Prolanis in treating Type 2 DM. Analytical cross-sectional research using secondary data from BPJS Kesehatan in the Sibolga Branch Office work area in 2020-2022 on Type 2 DM participants who took Prolanis and Non-Prolanis. The analysis used univariate, bivariate, multiple logistic regression, and ICER cost analysis. Characteristics of Prolanis participants, age, number of visits, and Body Mass Index showed a significant relationship with the achievement of controlled fasting blood sugar. The average fasting blood sugar of Prolanis and Non-Prolanis participants in 2021-2022 did not significantly differ. Still, the proportion of controlled fasting blood sugar of Prolanis participants was greater than that of Non-Prolanis participants. The total cost of Prolanis in a row for 2020-2022 is IDR 1,437,411,273, IDR 2,706,895,281, and IDR 2,751,510,452. The total cost of Non Prolanis for 2020-2022 is IDR 5,861,773,361; IDR 7,807,455,547,-; IDR 10,291,812,544,-. The ICER for each controlled fasting blood sugar proportion varies from 2020-2022 IDR 462,489; IDR 201,473;  IDR 362,856. Prolanis expenditure at the Sibolga Branch Office is higher, but the clinical effectiveness of the proportion of controlled fasting blood sugar participants is better than that of non-Prolanis participants